Pengembangan Video Pembelajaran Berbasis Animasi Powtoon pada Materi Teknik Dasar Memasak untuk Siswa Kuliner Fase E - Gloria Norenta; Andika Kuncoro Widagdo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research is a product development study in the form of an animated video based on Powtoon, focusing on basic cooking techniques. The aims of this study are to: 1) identify the development results of the Powtoon-based animated instructional video on basic cooking techniques; 2) determine the feasibility of the Powtoon-based animated video on basic cooking techniques; and 3) assess students' responses to the Powtoon-based animated video on basic cooking techniques. This study employs the 4D development model, limited to the Development stage. Data were collected through material validation sheets, media validation sheets, and student response questionnaires using a Likert scale. The validation sheets were assessed by expert judgment, and the results were calculated using the Aiken's V formula. Based on the data analysis, the material expert validation score was 0.79, the media expert validation score was 0.92, and the student response score was 84.15%. These results indicate that the Powtoon-based animated video on basic cooking techniques is feasible for use.